Increasing intake of dietary soluble nutrients affects digesta passage rate in the stomach of growing pigs. Issue 5 (30th January 2019) - Schop, Marijke; Jansman, Alfons J. M.; de Vries, Sonja; Gerrits, Walter J. J.
Abstract: The passage rate of solids and liquids through the gastrointestinal tract differs. Increased dietary nutrient solubility causes nutrients to shift from the solid to the liquid digesta fraction and potentially affect digesta passage kinetics. We quantified: (1) the effect of three levels of dietary nutrient solubility (8, 19 and 31 % of soluble protein and sucrose in the diet) at high feed intake level (S) and (2) the effect of low v. high feed intake level (F), on digesta passage kinetics in forty male growing pigs. The mean retention time (MRT) of solids and liquids in the stomach and small intestine was assessed using TiO2 and Cr-EDTA, respectively. In addition, physicochemical properties of digesta were evaluated. Overall, solids were retained longer than liquids in the stomach (2·0 h, P <0·0001) and stomach+small intestine (1·6 h, P <0·001). When S increased, MRT in stomach decreased by 1·3 h for solids ( P =0·01) and 0·7 h for liquids ( P =0·002) but only at the highest level of S. When F increased using low-soluble nutrients, MRT in stomach increased by 0·8 h for solids ( P =0·041) and 0·7 h for liquids ( P =0·0001). Dietary treatments did not affect water-binding capacity and viscosity of digesta. In the stomach of growing pigs, dietary nutrient solubility affects digesta MRT in a non-linear manner, while feed intake level increases digesta MRT depending on dietary nutrient solubility. Results can be used to improve predictions on the kinetics of nutrient passage and thereby of nutrient digestion and absorption in the gastrointestinal tract.